The Effectiveness Of Elderly Exercise In Decreasing The Level Of Insomnia - Eri Fauziah; Sri Hartati; Kamesyworo (Journal of Applied Nursing and Health, 2022)
Background: Aging is not a disease for the elderly and is not an obstacle to being able to maintain productivity and independence in carrying out daily life days. However, entering old age, many experience physical and mental setbacks, which can cause problems with disease, depression, and sleep disturbances. The purpose of this study was to determine the effectiveness of elderly exercise in reducing the level of insomnia in the elderly Methods: The research method used is the  Quasy Experimental with the design one-group  Pretest-Posttest  population is the elderly who experience insomnia in Posbindu Pesona UPT Puskesmas Agel Lahat with a sample of 50 respondents  They were taken on the total side. Data were collected from respondents by distributing questionnaires before and after counseling to respondents. Results: The results showed that the initial observation found that 50 41 respondents (82%) had moderate insomnia after being given the elderly exercise technique. 46 respondents (92%) with mild insomnia and four (8%) with moderate insomnia experienced mild insomnia. The results of the Defendant T-Test showed significant results P = 0.00. This shows the effect of the Effectiveness of the Elderly Gymnastics Technique on the reduction of Insomnia Levels. Conclusion:  There is a significant difference in the level of insomnia in elderly mothers between before being given the elderly exercise technique and after being given the elderly exercise technique.